CRIMINAL LAW PROTECTION OF THE DIGNITY AND HONOUR OF AUTHORITIES - N. B. Gulieva (Вестник Кемеровского государственного университета, 2013)
The paper is devoted to studying criminal laws defining the corpus delicti for crimes that infringe on the dignity and honour of authorities. It aims at pointing out some contradictions in the criminal laws under consideration, making recommendations to the legislators to improve some of their provisions, and helping law enforcers to duly interpret the content of the laws criminalizing the infringement on the dignity and honour of authorities. The study uses analysis, synthesis and comparative law methods. It can be applied in law enforcement, academic research and in teaching. As a result of the study, the author concludes that the legislators should use unified criteria for the criminal law protection of the honour and dignity of authorities, avoiding contradictory formulations in criminal laws.